European cohesion policy after 2006:some comments about current proposals - Olga Ogando; Beatriz Fari\~na (European Regional Science Association (ERSA), 2004)
EU regional policy is in a challenging and dynamic period of change. Not only are there significant administrative problems to overcome in both the current and the new Member States, but there is also a major ongoing debate about the reform of EU regional policy after 2006. Post 2006, the principal challenge concerns economic and social cohesion in an enlarged Union. Enlargement will lead to a severely unbalanced EU territory in terms of the widening disparities between Member States and regions. The degree to which EU regional policy can meet these challenges will be determined by budgetary constraints. The period of successive increases in EU regional policy ended at the Berlin Council in March 1999. Aspects of the current debate concern not only the EU regional policy budget for 2007-2013 but also the possible allocations. In this context, the paper has two main objectives: a) To identify regional disparities in the forthcoming enlarged Europe using multivariate statistical analysis techniques. b) To assess different proposals arising from the Commission open debate on future Cohesion Policy. The data used in the analysis is Newcronos-REGIO database elaborated by EUROSTAT. As a result, a classification of all regions (NUTsII) in the EU-25 is obtained through factor and cluster analysis techniques. Results obtained show that regional disparities cannot be exclusively explained by GDP per capita. Other factors linked to the behaviour of the labour market and to the demographic characteristics of the territories are also of a great importance Key words: Economic and Social Cohesion, Regional Policy, Cluster Analysis
Keywords: 330; Economic and Social Cohesion; Regional Policy; Cluster Analysis